Tourism planning in the Azores and feedback from visitors - João Crispim Ponte; Gualter Couto; Pedro Pimentel; Áurea Sandra Toledo de Sousa; André Oliveira (Tourism & Management Studies)
Tourism planning is increasingly a fundamental process for qualifying and increasing the competitiveness of tourist destinations, especially when it is required to take into account the new needs of tourists and the global trend towards meeting the principles of sustainable tourism. This study aims to analyse the improvements that, in the opinion of visitors, should be implemented in Ponta Delgada, the largest hub of tourism activity in the Azores (Portugal), detecting differences between specific groups of visitors, in order to contribute to territorial organisation and the optimisation of tourism experiences. 400 answers to a survey distributed among tourists who visited this Azorean municipality were analysed, using several statistical methods, such as the chi-square test of independence and some Hierarchical Cluster Analysis algorithms. The main conclusions refer to the statistically significant associations between the mean of transport used to travel and views of some aspects to be improved, with signs of patterns in visits and critical attitude.